Impact of Information Transparency on BankingService Quality and Public Satisfaction in Digital Era - Sri Harmila; Amalia Az zahra; Rio Septian Tarigan; Fina Naini (PT. Altaf Publishing Corp, 2025)
In the current era of computers and the internet, information transparency has become one of the key components that determine how good banking services are and how satisfied the public is with them. Banks provide open information to customers, enhancing trust and loyalty. The impact of information transparency on public satisfaction and the quality of banking services is the subject of this study. To gather data, a survey was conducted with customers from various banks that actively use digital services. The analysis results indicate that the more transparent a bank is, the better customers' perceptions of service quality, particularly in terms of product information clarity, ease of access, and protection of personal data. Banks must continue to innovate in providing clear, accurate, and easily accessible information to strengthen their relationship with customers, as information transparency improves public satisfaction and enhances the bank's competitiveness in the digital banking industry.